Empowering Muslim Rohingya Youth Refugees: A Baseline Study of Literacy - Mohd Ali, Suraini; Baharun, Hazleena; Abdullah, Hazlina; Baharudin, Dini Farhana; Zakaria, Mohd. Zaliridzal; Ismail, Habibah; Mat Saad, Noor Saazai; Behak, Fariza Puteh (‘Abqari Journal, 2020)
In adult refugees’ context, functional literacy is the biggest barrier for the refugees to socially navigate in the host community. Functional literacy is ‘the level of skill in listening, speaking, reading and writing that any individual needs in order to cope with adult life.’ Without functional literacy abilities in the language/s of the host country and uncertainties in the journey to resettlement, the refugees tend to become very vulnerable and traumatized. Thus, social navigation for survival becomes an issue not only because they have language barriers but also internal conflicts on the terrains of the imagined (the hopes) and the unexpected (the difficulties) they encounter in the host country. Employing both qualitative and quantitative data collection tools, this study explored the current English language literacy ability of the Rohingya youth refugees and related challenges. Findings revealed that despite the keen interests the participants have in acquiring English language proficiency, the different alphabetical systems pose problems for them. Despite the challenges in language, the participants exhibited strong sense of brotherhood with other fellow refugees and willingness to extend assistance. Religion developed the powerful bond. Based on the empirical data gathered, a Functional Literacy Course was developed to address language issues embedded with Leadership as well as Islamic Psycho-spiritual elements.